Dynamic numerical simulation and risk predictive assessment of the slope debris flow for the rear mountain at the management office of the Erlang Mountain Tunnel - Wang, Hao; Dai, Lin; Pan, Deng; Yue, Jianwei; Fu, Dewei; Yan, Tiantian (Frontiers in Earth Science, 2022)
The Erlang Mountain Tunnel Management Office is located in Luding County, Sichuan Province, China. A long-term open-pit limestone mine is located on the rear mountain, 1 km from the west entrance of the Erlang Mountain Tunnel Management Office for the Sichuan-Tibet Highway. Dangerous rock masses and a large accumulation of mine waste slag are present on the hillside, which can easily produce slope debris flow disasters. This paper analyzes the formation causes of slope debris flow through field investigation and uses RAMMS (Rapid mass movement simulation) software to study the influence of base friction coefficient μ and ξ on slope debris flow. Numerical simulation predicted level of danger of the movement process from the aspects of Velocity, deposition height, flow, topography. When the dry Coulomb friction value μ increased from 0.3 to 0.4, the debris velocity decreased and began to spread out along the slope. The flow process can be divided into four parts, and found that the velocity and discharge are different in the upstream and downstream of the slope constriction. The slope constriction has a significant amplification effect on the velocity and discharge. The velocity is amplified by 31.1%, and the discharge is amplified by 14.5%. In addition, based on the dynamic characteristics and the frequency of rainstorms, the risk of debris flow is divided into four levels: low, medium, high, and extremely high. The hazard map of slope debris flow in the rainstorm return period (20 years) is established, which provides a basis for the assessment and prediction of debris flow.